Panfacial fracture osteosynthesis combined with submental orotracheal intubation: A case report (Research, Society and Development, 2024)
Panfacial fractures can be a surgical challenge due to bone instability and loss of facial landmarks. Accurate diagnosis and planning favor the correct restoration of facial architecture. Good results depend on the acquisition of occlusal relationships, which is difficult in classic orotracheal intubation. Thus, submental bypass is an interesting way of maintaining the airway during surgery and simultaneously allowing occlusal contacts. This study aims to evaluate multiple facial osteosyntheses in a patient with panfacial fracture, for whom submental orotracheal intubation was chosen by means of a case report. A 29-year-old male patient, victim of a car accident, presented trismus, dystopia, enophthalmos, occlusal changes, hyposphagma, bilateral periorbital ecchymosis, loss of the anteroposterior projection of the face and pain. The imaging examination showed multiple fracture patterns, which characterized a panfacial fracture. Orotracheal intubation with submental bypass was performed to improve osteosynthesis results and guarantee air permeability. “Bottom-up” and “outside-in” reconstruction sequences were chosen through coronal access with left preauricular extension and subtarsal and intraoral vestibular approaches. The procedure was uneventful and the signs and symptoms were cured. Proper planning in complex cases, such as panfacial fractures, allows adequate resolution and satisfactory aesthetic-functional results. Furthermore, submental orotracheal intubation is safe and can be an interesting and valuable ventilation alternative.